Short-Term Effects of Isometric Quadriceps Muscle Exercise with Auditory and Visual Feedback on Pain, Physical Function, and Performance after Total Knee Arthroplasty: A Randomized Controlled Trial - Kondo, Yasutaka; Yoshida, Yoshihiro; Iioka, Takashi; Kataoka, Hideki; Sakamoto, Junya; Hirase, Tatsuya; Honda, Yuichiro; Nawata, Atsushi; Okita, Minoru (The Journal of Knee Surgery, 2020)
Severe acute pain after total knee arthroplasty (TKA) may cause delay in muscle strength and functional recovery, and it is a risk factor for chronic postoperative pain. Although pharmacological approaches are the typical firstline to treat acute pain; recently, nonpharmacological approaches such as exercise have been increasingly applied. The purpose of this investigation was to evaluate the effects of a rehabilitation program involving isometric quadriceps exercise with auditory and visual feedback to improve the short-term outcome after TKA. Sixty-two patients, planning a primary unilateral TKA, were randomly assigned to either an intervention group (n = 31) involving isometric quadriceps exercise with auditory and visual feedback in usual rehabilitation after TKA or a control group (n = 31) involving a standardized program for TKA. Patients in the intervention group performed the isometric quadriceps muscle exercise using the Quadriceps Training Machine from 2 to 14 days after TKA instead of the traditional quadriceps sets. Pain intensity, isometric knee extension strength, range of motion, timed up and go test (TUG), 10-m gait speed, 6-minute walking distance, the Western Ontario and McMaster University Osteoarthritis index (WOMAC), the hospital anxiety and depression scale, and the pain catastrophizing scale were assessed before TKA (baseline) and 1 to 3 weeks after TKA. Pain intensity significantly decreased in the intervention group than in the control group at 1 (p = 0.005), 2 (p = 0.002), and 3 (p = 0.010) weeks after TKA. Greater improvements in TUG (p = 0.036), 10-m gait speed (p = 0.047), WOMAC total score (p = 0.017), pain (p = 0.010), and function (p = 0.028) 3 weeks after TKA were observed in the intervention group. These results suggest that isometric quadriceps exercises with auditory and visual feedback provided early knee pain relief, possibly leading to better improvements in physical performance, and patient's perception of physical function in the early stages of postoperative TKA. Further studies should investigate whether this short-term effect is sustainable.
Keywords: total knee arthroplasty; postoperative pain; auditory and visual feedback; task; attention